Seismic Evidence of an Early Afterslip During the 2012 Sequence in Emilia (Italy). Issue 2 (16th January 2019) - Sugan, M.; Vuan, A.; Kato, A.; Massa, M.; Amati, G.
Abstract: We apply a matched‐filter‐technique to augment the detected events in the time window between the two mainshocks of the 2012 Emilia seismic sequence (Italy), 20 (Mw 6.1) and 29 (Mw 6.0) May. Using well‐located templates, we increase the number of detections from 1, 727 to 7, 616. This greater detail allows evidencing migrations of seismic events from the nucleation point of the first shock to the second. Repeating earthquakes are also found between the two mainshocks. The seismicity pattern suggests a transient slip acting immediately after the shallow first event, weakening and loading the volume around the deep nucleation point of the 29 May Mw 6.0 earthquake. We interpret migrations and repeaters as the fingerprint of an early afterslip triggered by the first mainshock. By taking into account the earliest repeater we estimate a cumulative slip of approximately 27 cm (Mw 5.7). This value could represent the lower bound of the total released afterslip. Plain Language Summary: To improve our understanding of interactions between subsequent mainshocks, we investigated the spatiotemporal evolution of the seismicity for the 2012 Emilia seismic sequence (Italy) in the time window from 20 to 29 May 2012. We use a technique based on waveform matching to augment the detected earthquakes. From the new catalog, we observe along‐strike and at depth seismic migrations consistent with a phase of rapid postseismic slip concentrated near the base of the seismogenic zone immediately after the first main shock. We suggest that the afterslip contributed to loading the fault rupture area of the 29 May Mw 6.0 earthquake. Key Points: Newly detected early aftershocks suggest a fast migration at depth moving from the 20 May hypocenter to the 29 May nucleation point Repeating earthquakes have been identified between the two mainshocks Migration and repeaters suggest an afterslip that could have contributed to loading the 29 May focal volume